Does adopting the bean technology bundle enhance food security and resilience for smallholder farmers in Ethiopia? - Katungi, Enid; Habte, Endeshaw; Aseete, Paul; Rubyogo, Jean Claude (MDPI, 2024)
The analysis of the differential impacts of multiple improved technologies has largely accounted for selective adoption, considering either the full application of a bundle or its individual components. The impacts of adopting agricultural technology bundles on household welfare are less understood when considering a partial adoption of either the entire bundle or its individual components on a portion of crop area. We assess simultaneous adoption and the impacts of multiple improved technologies promoted as a bundle and recommended for legume intensification systems for smallholder farmers in Ethiopia. We use DNA fingerprinting data to precisely identify our key treatment—“adoption of improved bean varieties”—in this study. Using an endogenous multivariate treatment effects model, we found significant positive impacts of adopting bundled interventions on agricultural incomes and household food security but vulnerability to food insecurity persists for many households. We find that growing improved varieties with fertilizers increased household agricultural revenue, allowing for more legume consumption and enhancing their likelihood of achieving adequate food consumption and food security outcomes; however, the vulnerability to food insecurity of the adopters remains high due to pre-existing resource degradation issues. Given the similarity in production contexts in Sub-Saharan Africa, our results provide perspective for similar development interventions. We use the results of our analysis to discuss potential policy implications and programs to support technological intensification among smallholder farmers.